HEC Forum HealthCare Ethics Committee Forum: An Interprofessional Journal on Healthcare Institutions' Ethical and Legal Issues - Cherry, Mark J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
HEC Forum is an international, peer-reviewed publication featuring original contributions of interest to practicing physicians, nurses, social workers, risk managers, attorneys, ethicists, and other HEC committee members. Contributions are welcomed from any pertinent source, but the text should be written to be appreciated by HEC members and lay readers. HEC Forum publishes essays, research papers, and features the following sections: Essays on Substantive Bioethical/Health Law Issues Analyses of Procedural or Operational Committee Issues Document Exchange Special Articles International Perspectives Mt./St. Anonymous: Cases and Institutional Policies Point/Counterpoint Argumentation Case Reviews, Analyses, and Resolutions Chairperson's Section `Tough Spot' Critical Annotations Health Law Alert Network News Letters to the Editors.
Keywords: Ethics; Medicine -- Philosophy; Medical ethics; Medical laws and legislation; Ethics; Medical Law; Philosophy of Medicine; Theory of Medicine/Bioethics.